Description of a new species of crayfish in the genus Faxonius (Decapoda: Cambaridae) from the Lower Ohio River Drainage, with evidence of glacial influence on the distribution of some crayfish species throughout the Ohio River basin - Couch, Zachary L.; Hayes, David M. (Zootaxa, 2022)
Variation in morphology of Faxonius jeffersoni has been documented since the 1960’s. However, a taxonomic review of the species had not been conducted. In order to clarify if F. jeffersoni exhibited a variety of character traits, or was comprised of multiple taxa, genetic and morphological analyses were conducted. As a result, we revealed that F. jeffersoni sensu lato was comprised of two non-sister taxa. A new species of crayfish, Faxonius elix n. sp., is described herein. Further analysis shows evidence of glacial influence on the distribution of crayfish species of the genus Faxonius throughout Kentucky, Illinois, and Indiana along the glacial maximum.